Phytochemical and bioactivities of Malaysian Artocarpus lowii king, A. Scortechinii king and A. Teysmanii MIQ. - Jamil, Shajarahtunnur (2006)
Phytochemical studies of Artocarpus lowii King, A. scortechinii King and A. teysmanii Miq. have resulted in the isolation of four new compounds and eight known compounds. Three new compounds have been successfully isolated from A. lowii King, i.e 2',4'-dihydroxy-4-methoxy-3'-prenyldihydrochalcone, 2',3,4',4-tetrahydroxy-3'- prenylchalcone and 2-hydroxyparatocarpin C. Three known compounds were identified as cycloheterophyllin, 2',4',4-trihydroxy-3'-prenylchalcone and 4-hydroxylonchocarpin. Methylation of 2',4'-dihydroxy-4-methoxy-3'-prenyldihydrochalcone and 2',4',4- trihydroxy-3'-prenylchalcone gave 2',4',4-trimethoxy-3'-prenyldihydrochalcone and 2'-hydroxy-4',4-dimethoxy-3'-prenylchalcone, respectively while methylation of cycloheterophyllin gave mixtures of dimethoxy and trimethoxy derivatives. Acetylation of cycloheterophyllin afforded cycloheterophyllin diacetate. A new compound was isolated from A. scortechinii King and was identified as 2',4',5',5-tetrahydroxy-3-geranyl-7,8-(2,2-dimethyl-6H-pyrano)-6-prenylflavone together with three known compounds, i.e artonin E, artobiloxanthone and lupeol 3-acetate. Methylation of artonin E gave artonin E trimethyl ether while acetylation of artonin E afforded artonin E tetraacetate. Four known compounds were isolated from A. teysmanii Miq., which were identified as artonin E, artobiloxanthone, artonol B and cycloartobiloxanthone. The structures of all compounds were established based on spectral studies using nuclear magnetic resonance spectroscopy, mass spectrometry, infrared spectroscopy and ultraviolet spectroscopy. The biological studies on the crude extracts and pure compounds of these three species showed that several pure compounds have significant biological activity especially in the antioxidant, platelet aggregation and cytotoxicity assays. Cycloheterophyllin and artonin E showed high ability to act as free radical scavengers with scavenging concentration values of 51.6 ug/mL and 48.3 ug/mL, respectively. Cycloheterophyllin, artonin E, isobavachalcone and 2',4'-dihydroxy-4-methoxy-3'-prenyldihydrochalcone totally inhibited adenosine diphosphate-induced platelet aggregation compared to standard aspirin which suppressed only 31.6% of the platelet aggregation. Cyloheterophyllin and artonin E were found to be active against breast cancer cell line, MCF7 comparable to the standard tamoxifen citrate. Finally, 2'- hydroxy-4,4',6'-trimethoxy-3'-prenylchalcone was synthesized through a three step synthesis. The steps involved Friedel-Crafts prenylation followed by methylation and Claisen-Schmidt condensation. Oxidative cyclization of this chalcone yielded an aldehyde-type chalcone derivative. 2'-Hydroxy-4-methoxy-4'-O-prenylchalcone was synthesized through a two steps synthesis involving Friedel-Crafts prenylation followed by Claisen-Schmidt condensation. Attempted Claisen rearrangement produced 4'-hydroxy-4-methoxy-2'-O-prenylchalcone as the major product.